Augmented reality-based flashcard media to improve students' concept understanding in chemistry learning - Izzati, Latansa Naelal; Kamaludin, Agus (Indonesian Journal of Science and Mathematics Education, 2024)
The reaction processes in voltaic cells are abstract, so media is needed to visualize them. This research aims to develop flashcard media based on augmented reality using voltaic cell material. This research uses the ADDIE model, including analysis, design, development, implementation, and evaluation. The research instruments used were product quality assessment sheets and student response sheets. Based on the results of assessments from material experts, media experts, reviewers, and student responses, ideal percentages were obtained at 90%, 89.23%, 90.58%, and 98.3%. Based on the assessment results, it can be concluded that augmented reality-based flashcard learning media is included in the very feasible category. It can be used as an alternative media to increase students' understanding of concepts in voltaic cell material. This research emphasizes developing learning media by utilizing technological advances.